The Influence of Science Technology Engineering Arts Mathematics-Based Psychological Capital Combined With Ideological and Political Education on the Entrepreneurial Performance and Sports Morality of College Teachers and Students - Jin, Ying (Frontiers in Psychology, 2022)
This study aims to alleviate the current tense employment situation and study the entrepreneurial situation of teachers and students in colleges and universities. Firstly, based on the educational concept of Science Technology Engineering Arts Mathematics (STEAM), Ideological and Political Education (IPE) is added to psychological capital to explore the effect of the combination of the two on entrepreneurial performance. An entrepreneurial performance impact model is constructed, and the questionnaire is set. Secondly, the influence of psychological capital combined with IPE on sports morality is explored, and a sports morality questionnaire is designed. Finally, the questionnaire results are analyzed. The results showed that most of the participants in the survey are under the age of 25. The 25- to 29-year-olds are the smallest among those surveyed. The respondents who participated in the survey had the most undergraduate degrees, accounting for 43.4%. The 40 items on entrepreneurial performance this time obey a normal distribution, and the scale has good reliability and validity. The main factor analysis results obtained by principal component analysis include 6 factors. Their total explanatory power exceeds 67%, and the six factors screened out this time are well represented. The model tolerance is between 0.45 and 0.5, and the Variance Inflation Factor (VIF) value is less than 10. The scale does not suffer from multi-collinearity issues. IPE significantly strengthens the effect of psychological capital on entrepreneurial performance. The influences of various sports on sportsmanship, bravery, self-confidence, and self-transcendence are significantly different, and the P value is less than 0.001. The difference in aggressiveness is less than 0.01, indicating that it is very significant. Different sports have significant differences in the cultivation of sports morality, and the P value is less than 0.05. The differences in self-discipline are also significant, and there are extremely significant differences in compliance with rules, and the P value here is less than 0.001. There are no significant differences in sporting qualities. IPE combined with psychological capital has a significant impact on entrepreneurial performance.